La competencia constitucional de los jueces ordinarios y su incidencia en el control de constitucionalidad en el ecuador - Morales Alarcón, Diego Orlando (2023)
Faced with the current situation that the administration of justice is going through in our country, it is necessary to debate in depth the need for specialization of constitutional judges, who address said jurisdictional guarantees, or constitutional actions; It is also necessary in the face of abuse of the right on some occasions, in the presentation of these guarantees to establish their true purpose, to know their beginning, the requirements and the procedure embodied in the Constitution of 2008 and in the Organic Law of Jurisdictional Guarantees, but which has an explicit jurisprudence from some years ago since 1997, the same one that helps us to delve into the debate of the state that guarantees rights; Ecuador, being a Constitutional State of rights and justice, which implies that all citizens in general are under this explicit mantle of human rights and guarantees, which coexists with the mixed constitutional control that exists, from my point of view, in our country. , it is necessary to analyze and investigate the constitutional role of first instance judges or ordinary judges, in relation to their constitutional competence; It must be clear that the protection that is sought through jurisdictional guarantees, are executed, are reflected and not only remain in mere sentences for review in the Constitutional Court but that they are part of the acquis of Constitutional Procedural Law, for this reason the proposal is the existence through a legislative reform of Specialized Constitutional Judges.